Establishing the Basic Concepts of a Healthy Physical Education through an Expert Method - Carlos Javier López Gutiérrez; Alexis Juan Stuart Rivero; Anairis Granado Mejías (Universidad Autónoma de Baja California, 2011)
This paper investigates the basic knowledge needed by the sports practitioner who wishes to have a healthy physical education. To determine the necessary basic knowledge, we used a methodology of standard expertise, delving further into the subject by means of a semistructured interview. The interview was taped, transcribed and analyzed through the program Nudist NVivo. We have grouped the common responses emerging from the analysis into different categories, thus obtaining a total of 9 basic considerations which should be habitually transmitted to Physical Education students, so that they may achieve adequate self-management in the practice of physical activity.